Students Perspective in Learning Procedure Text through Video Assignments of the Merdeka Curriculum in Grade 11 SMAN 1 Gedangan - Salsabila, Farikha; Soraya, Irma; Mujiono, Muhammad (ICONELT, 2024)
Video assignment can help language learners to practice and improve their speaking skills. This study aims to find out grade XI student’s perspectives on the use of video assignments as a method of learning procedure texts in Merdeka Curriculum. Data were collected from grade XI students of SMAN 1 Gedangan using a qualitative approach with a case study method to explore student’s perspectives towards learning procedure text through video assignments in Merdeka Curriculum. Case studies were chosen because they allow researchers to understand student’s experiences in depth within a specific learning context. In this study, data is collected through interviews, observations and questionnaires as well as analysis of project results that have been made by students. The data collected in this study will be analyzed using thematic analysis to identify patterns and themes that emerge from interviews, observations, and analysis of student projects. This research focuses on how students perceive video assignments to be effective, interesting and difficult to improve their understanding of procedure texts. The analysis results show that most students find it easier to understand procedure texts when they practice the steps of procedure texts directly through videos. However, other students stated that they found it difficult in finding creative ways to convey the steps of the procedure text. Thus, before starting the video shooting, most students prepared a draft before shooting the English video. Most students had difficulties in grammar when speaking English. Through this video assignment, the students were able to improve their speaking skills in an easier way and allowed the students to be creative and have a better understanding of the procedure texts. This research is useful for educators who are considering incorporating video assignments in English learning of Merdeka Curriculum.